2017
DOI: 10.1002/bimj.201600084
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐finding methods for Phase I clinical trials using pharmacokinetics in small populations

Abstract: The aim of phase I clinical trials is to obtain reliable information on safety, tolerability, pharmacokinetics (PK), and mechanism of action of drugs with the objective of determining the maximum tolerated dose (MTD). In most phase I studies, dose‐finding and PK analysis are done separately and no attempt is made to combine them during dose allocation. In cases such as rare diseases, paediatrics, and studies in a biomarker‐defined subgroup of a defined population, the available population size will limit the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 27 publications
0
74
0
Order By: Relevance
“…A 3 + 3 design is commonly used in phase I trials due to its simple, intuitive, and pre-specified escalation rules. However, the 3 + 3 method has been criticized for being conservative because the method is dictated by the observed DLT rate without acknowledging the variability arising from a small cohort size [19]. Like the 3 + 3 design, the mTPI method incorporates pre-specified escalation rules.…”
Section: Discussionmentioning
confidence: 99%
“…A 3 + 3 design is commonly used in phase I trials due to its simple, intuitive, and pre-specified escalation rules. However, the 3 + 3 method has been criticized for being conservative because the method is dictated by the observed DLT rate without acknowledging the variability arising from a small cohort size [19]. Like the 3 + 3 design, the mTPI method incorporates pre-specified escalation rules.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of pharmacokinetics (PK) and pharmacodynamics (PD) data in early-phase dose-finding studies Meta-analysis methods for small trials or small numbers of trials Key publications: [25,[27][28][29][30] Key publications: [33, 34, 36-38, 40, 41] Open-source R software: dfpk [26], dfped [29] Open-source R software: bayesmeta [35], nmaINLA [42] and meta-analysis methods for small trials or small numbers of trials. The work in these four areas is described below.…”
Section: Improved Analysis and Evidence Synthesismentioning
confidence: 99%
“…These models utilize both dose and PK assessment. Ursino et al (2017) compared the operating characteristics of the previously mentioned approaches in a simulation study and found that these methods did not improve the effectiveness of dose‐finding trials . These approaches have rarely been used in practice because they do not increase the rate of correct OD selection.…”
Section: Introductionmentioning
confidence: 99%
“…Ursino et al (2017) compared the operating characteristics of the previously mentioned approaches in a simulation study and found that these methods did not improve the effectiveness of dose-finding trials. 11 These approaches have rarely been used in practice because they do not increase the rate of correct OD selection. Possible reasons are multi-collinearity between dose and PK information, the nonproportional relationship between dose and PK information at higher dose levels, and large inter-individual variability.…”
Section: Introductionmentioning
confidence: 99%